GURU PENDIDIKAN AGAMA KRISTEN SEBAGAI MENTORING BAGI KORBAN BULLYING - Sumarno, Yuel; Suji, Kornelia; Jhoni Hardori (Edukasi : Jurnal Pendidikan Agama Kristen, 2021)
Feelings of being worthless and under pressure make victims of bullying feel that they are not strong enough to go through school. Teachers try to be able to open the way of thinking that makes them victims, changing them is valuable. This research invites readers to see how big the impact is on those who experience bullying. The method used uses library research where all data comes from books and scientific articles. The analysis obtained shows that a teacher must act as a mentor who can help students get out of their problems, so that they can reawaken their fighting power to go to school.